2020
DOI: 10.14198/jhse.2021.161.13
|View full text |Cite
|
Sign up to set email alerts
|

Impact of exercise intervention on anxiety levels and mood profile of Greek prison inmates

Abstract: Imprisonment is clearly associated with mental health problems among prisoners. Evidence across research literature shows that exercise in detention environments improves mental health. The purpose of the study was to examine the effect of an exercise program on mood profile and anxiety of inmates in Greek prisons. Sixty male inmates randomly assigned in two groups (control and experiment). Individuals of the exercise group received a 12 weeks training program at a frequency of three (3) training sessions each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Psychou study (2020) illustrated that the exercise program is beneficial on mood profile which can reduce the anxiety and stress level. 6,10 In addition, some important findings were found in this study. Our findings illustrated that heart failure patients face harsh emotional challenges, particularly anxiety which may have led to negative health outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…Psychou study (2020) illustrated that the exercise program is beneficial on mood profile which can reduce the anxiety and stress level. 6,10 In addition, some important findings were found in this study. Our findings illustrated that heart failure patients face harsh emotional challenges, particularly anxiety which may have led to negative health outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…The studies were a mix of randomized and non-randomized trials. In one randomized trial, researchers measured state anxiety levels in 37 prisoners after the exercise group completed a six-week interval exercise training program [ 11 ]; another randomized trial measured depression, state anxiety, and trait anxiety in 60 prisoners after the exercise group underwent a 12-week exercise program [ 12 ]. In a non-randomized trial, depression and anxiety were measured in 30 prisoners with pre-existing mental health symptoms after the exercise group completed a three-month exercise program [ 13 ]; another non-randomized trial measured somatization, anxiety, social dysfunction, and severe depression in 97 prisoners, where the individuals in the exercise group exercised at least three times each week [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Exercise. Eight studies measured the effect of various forms of exercise on mental health outcomes [11][12][13][14][15][16][17][18]. While most studies examined exercise conducted in group settings, the interventions described all indicated that the activity would be possible to perform on one's own, without an activity facilitator, and all measured outcomes at the individual level were not likely to have been obtained as part of a group experience.…”
Section: Plos Onementioning
confidence: 99%
“…In particular, self-ratings of physical strength are relative (“compared with my peers”) rather than absolute and are therefore probably affected by rank order fluctuation, especially considering the hierarchical structure of prison society (Ugelvik, 2014 ; Kreager et al, 2017 ) as noted previously. Also, although the sample size appears low, it is justified by power analysis and is equivalent to the preponderance of samples from similar interventions on this topic (Mohan et al, 2018 ; Legrand et al, 2020 ; Pralong et al, 2020 ; Psychou et al, 2020 ; Papa et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The prison setting is ideal for physical activity interventions as there is an absence of important barriers to physical activity such as cost, insufficient time, partner and family commitment and issues, absence of equipment, and transportation to training facilities (Plugge et al, 2011 ; Parker et al, 2014 ; Jones et al, 2021 ). Physical activity interventions among prisoners have been associated with increased physical health and strength, higher self-esteem and self-efficacy, improved mood and reduced aggressive behavior, and enhanced mental health (Mohan et al, 2018 ; Psychou et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%